The Aga Khan Maqbara - Mumbai Archive Project Team (Jio Institute, 2024)
The Aga Khan Maqbara, also known as Hasanabad Dargah, serves as the final resting place of Aga Khan I, the honorific title of Hasan Ali Shah. He was the 46th Imam of the Nizari Isma'ili Shia Muslims and the first to bear the title of Aga Khan. He passed away in Mumbai in 1881.